Nonlinear Optical Tweezers As an Optical Method for Controlling Particles with High Trap Efficiency - Quy, Ho Quang (Communications in Physics, 2019)
Optical tweezers have seen as an essential tool for the manipulation dielectric microparticles and nanoparticles due to its non-contact action and high resolution of optical force. Up to now, there has been a lot of optical tweezers applications in the fields of biophysics, chemistry, medical science and nanoscience. Recently, optical tweezers have been theoretically and experimentally developing for the nanomechanical characterization of various kinds of biological cells. The configuration of optical tweezers has been day after day improving to enhance the trapping efficiency, spatial and temporal resolution and easy to control trapped objects. In common trend of optical tweezers improvements, we will discuss in detail of the several configurations of nonlinear optical tweezers using nonlinear materials as the added lens. We will also address the advantages of nonlinear optical tweezers, such as enhance optical efficiency, reduce trapping region, simplify controlling all-optical method. Finally, we present discussions about the specific properties of nonlinear optical tweezers used for stretch DNA molecule as example and an ideal to improve nonlinear  optical tweezers using thin layer of organic dye  proposed for going time.